2015
DOI: 10.1007/s11082-015-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the size-dependent permittivity of metal inclusions on the optical characteristics of a one-dimensional photonic crystal with a nanocomposite defect

Abstract: The spectral characteristics of a one-dimensional photonic crystal structure with a defect nanocomposite layer that consists of metallic nanoparticles distributed in a transparent matrix are theoretically studied. The defect mode shape inside the photonic band gap is found to depend substantially on the nanoparticle size and concentration in the defect layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The effective permittivity ( ) of silver nanoparticles embedded in is calculated using the Maxwell–Garnett model and is provided by the equation below: where , and are representing the filling fraction (percent) of NPs, Ag–NPs permittivity, and host material permittivity, respectively. The permittivity of Ag–NPs is then calculated using the Drude model 47 as where , and denote the high frequency limit of permittivity, Plasmon frequency, and damping frequency, respectively. At the same time, the radius of NPs(r) and the electron velocity at Fermi energy (v f ) have a crucial role in the nanoparticles damping frequency 34 .…”
Section: Theoretical Formulismmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective permittivity ( ) of silver nanoparticles embedded in is calculated using the Maxwell–Garnett model and is provided by the equation below: where , and are representing the filling fraction (percent) of NPs, Ag–NPs permittivity, and host material permittivity, respectively. The permittivity of Ag–NPs is then calculated using the Drude model 47 as where , and denote the high frequency limit of permittivity, Plasmon frequency, and damping frequency, respectively. At the same time, the radius of NPs(r) and the electron velocity at Fermi energy (v f ) have a crucial role in the nanoparticles damping frequency 34 .…”
Section: Theoretical Formulismmentioning
confidence: 99%
“…Furthermore, the use of NC materials in PCs may aid in the development of new PBGs 32 36 . It also allows reducing absorption values based on the volume fraction of the dispersive medium and the nanoparticles spherical radius 31 , 37 . Metal-dielectric NCs have recently been suggested as potentially appealing PC materials with unique plasmon resonance optical characteristics 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the effective permittivity is related to the structure and the properties of the composite materials, there are some inherent flaws in describing the physical properties of the additives in the medium [35]. Most of the theoretical researches are concerned with the volumetric fraction which cannot be determined accurately [36]. Most of the existing research work has not taken into account the influence of the frequency.…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 99%
“…As an example, nanocomposite (E7 + Ag-NPs) can tune the optical properties of 1DPS through variation of dielectric permittivity depending upon the size, shape and lling fraction of nanoparticles. The effective dielectric permittivity (function) or refractive index of NC can be calculated by using the Maxwell-Garnet model [43][44][45][46][47]. Vetrov et al [48] studied the optical Tamm states originating at the interface between the photonic crystals and NC containing core-shell structures, and reported that the Tamm states occur only for the negative value of the real dielectric permittivity of the NC layer.…”
Section: Introductionmentioning
confidence: 99%